Evaluation of the Effects of Photodynamic Therapy Alone and Combined with Standard Antifungal Therapy on Planktonic Cells and Biofilms of Fusarium spp. and Exophiala spp. - Gao, Lujuan; Jiang, Shaojie; Sun, Yi; Deng, Meiqi; Wu, Qingzhi; Li, Ming; Zeng, Tongxiang (Frontiers in Microbiology, 2016)
Infections of Fusarium spp. and Exophiala spp. are often chronic, recalcitrant, resulting in significant morbidity, causing discomfort, disfigurement, social isolation. Systemic disseminations happen in compromised patients, which are often refractory to available antifungal therapies and thereby lead to death. The antimicrobial photodynamic therapy has been demonstrated to effectively inactivate multiple pathogenic fungi and is considered as a promising alternative treatment for mycoses. In the present study, we applied methylene blue (8,16 and 32 μg/ml) as a photosensitizing agent and light emitting diode (635nm ± 10nm, 12 and 24 J/cm2), and evaluated the effects of photodynamic inactivation on five stains of Fusarium spp. and five strains of Exophiala spp, as well as photodynamic effects on in vitro susceptibility to itraconazole, voriconazole, posaconazole and amphotericin B, both planktonic and biofilm forms. Photodynamic therapy was efficient in reducing the growth of all stains tested, exhibiting colony forming unit-reductions of up to 6.4 log10 and 5.6 log10 against planktonic cultures and biofilms, respectively. However, biofilms were less sensitive since the irradiation time was twice longer than that of planktonic cultures. Notably, the photodynamic effects against Fusarium stains with high MIC values of ≥16, 4-8, 4-8 and 2-4 μg/ml for itraconazole, voriconazole, posaconazole and amphotericin B, respectively, were comparable or even superior to Exophiala spp., despite Exophiala spp. showed relatively better antifungal susceptibility profile. MIC ranges against planktonic cells of both species were up to 64 times lower after PDT treatment. Biofilms of both species showed high SMIC50 and SMIC80 of ≥16 μg/ml for all azoles tested and variable susceptibilities to AMB, with SMIC ranging between 1 and 16 μg/ml. Biofilms subjected to PDT exhibited a distinct reduction in SMIC50 and SMIC80 compared to untreated groups for both species, except SMIC80 of ITC against Fusarium biofilms. In conclusion, in vitro photodynamic therapy was efficient in inactivation of Fusarium spp. and Exophiala spp., both planktonic cultures and biofilms. In addition, the combination of PDT and antifungal drugs represents an attractive alternative to the current antifungal strategies. However, further investigations are warranted for the reliable and safe application in clinical practice.